TINJAUAN FIQH SIYASAH DUSTURIYAH TERHADAP IMPLEMENTASI UNDANG-UNDANG NOMOR 20 TAHUN 2003 DI ASRAMA AL-FAJR MA'HAD AL-ZAYTUN - Muhammad Abdul Jabar; Siti Ngainnur Rohmah; Abdur Rahim (STKIP Subang, 2024)
This thesis examines the realization of the implementation of a statutory regulation directly as a form of obedience to the Republic of Indonesia. Dormitories as a component of educational institutions must of course carry out activities in line with the goals and functions of national education as stated in article 3 of Law Number 20 of 2003 concerning the National Education System. This research aims to determine the implementation of Law Number 20 of 2003 Article 3 in the Al-Fajr Ma'had Al-Zaytun Dormitory. and a review of fiqh siyasah dusturiyah towards the implementation of Law Number 20 of 2003 Article 3 at the Al-Fajr Ma'had Al-Zaytun Dormitory. The method used in this research is a qualitative method where researchers make direct observations at the research location and conduct interviews with several sources who are one of the research objects. The research results show that the implementation of Law Number 20 of 2003 Article 3 has been well realized through the programs contained in Unsyithoh Yaumiyah. The attitudes and character of students, as well as national education goals, are formed through the activities and policies of dormitory management which are prepared systematically. And there were no hidden curricula or teachings that were not in accordance with the aims and functions of national education. From the perspective of siyasah dusturiyah fiqh, the implementation of Law Number 20 of 2003 is in line with Imam Al-Mawardi's theory of the formation of statutory regulations and is in line with the opinions of Ibnu Sina and Al-Maskawaihi regarding the goals of education. Keywords: Constitution, fiqh siyasah dusturiyah, Ma’had Al-Zaytun;